Long-term Follow-up of an Advanced Adult Periodontitis Case with Bite Collapse - Tsukamoto, Yumi; Watanabe, Ikuko; Minoura, Shingo; Inagaki, Koji; Amano, Katsuhiko; Suzuki, Miki; Maki, Eijiro; Noguchi, Toshihide; Murase, Motoyasu (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1996)
The present case report describes the outcome of collapsed bite with advanced periodontitis. A 47-year-old male with a noncontributory medical history was referred to our hospital in August of 1984, with a chief complaint of gingival swelling of the maxillary molars. A complete oral examination revealed the pronounced loss of periodontal attachment in most parts of the dentition, anterior spacing and crowding with the collapsed bite and the development of reduced height of the bite. Initial therapy was started with diagnosis of advanced adult periodontitis. Following completion of the initial therapy, periodontal surgeries for the deep pockets were performed on the most teeth. The number 2, 3, 4, 13, 14, 15 and 20 teeth were extracted during the periodontal surgical phase. After healing of the periodontal tissue, orthodontic treatment based on edgewise technique including bite opening, correction of crowding and space closure, was applied to reestablish esthetic and physiologic occlusion. After 1 year of orthodontic treatment, a maxillary lingual plate and a mandibular adhesion bridge were cemented. Following reevaluation of both the periodontal condition and craniomandibular status, the patient was recalled for maintenance care for about 12 years from an initial visit. In the maintenance phase, only 2 teeth were extracted and the prosthetic reconstruction was done. Mean probing depth and alveolar bone loss were improved from 4.1 mm and 63.8% to 2.6 mm and 45.9%, respectively. An attachment level of 6 mm has been maintained since 1989. As shown in this treatment procedure, we suggest that the comprehensive approaches to bite collapse with advanced periodontal breakdown may inhibit the progression of periodontal disease.